2012
DOI: 10.1089/ast.2011.0720
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Growth at the High Concentrations of Magnesium Sulfate Found in Martian Soils

Abstract: The martian surface environment exhibits extremes of salinity, temperature, desiccation, and radiation that would make it difficult for terrestrial microbes to survive. Recent evidence suggests that martian soils contain high concentrations of MgSO 4 minerals. Through warming of the soils, meltwater derived from subterranean ice-rich regolith may exist for an extended period of time and thus allow the propagation of terrestrial microbes and create significant bioburden at the near surface of Mars. The current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 58 publications
2
58
0
Order By: Relevance
“…Two of the isolates grew using sulfate as a terminal electron acceptor. Sulfate has been shown to be a major constituent of martian soils, and because sulfate systems exhibit high water activity, areas with sulfate salts are potentially more favorable to life (Crisler et al, 2012). Although neither selenium nor arsenic has been detected on Mars, various forms of arsenic and selenium are somewhat common on Earth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the isolates grew using sulfate as a terminal electron acceptor. Sulfate has been shown to be a major constituent of martian soils, and because sulfate systems exhibit high water activity, areas with sulfate salts are potentially more favorable to life (Crisler et al, 2012). Although neither selenium nor arsenic has been detected on Mars, various forms of arsenic and selenium are somewhat common on Earth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that salt tolerance would be required by microorganisms to survive and grow on Mars due to the high salt concentrations found in martian soils (Crisler et al, 2012). The majority of the isolates collected from MSL were able to grow in media containing elevated NaCl (93% of the isolates grew at ‡10% NaCl).…”
Section: Discussionmentioning
confidence: 99%
“…Martian soils were expected to be acidic, but the Phoenix Lander showed that the soils at its landing site were mildly basic with a pH of 7.7 ± 0.5 [17]. Salt tolerance would be required for life to survive and grow on Mars due to the high salt concentrations found in Martian soils in the form of NaCl, MgSO 4 , CaSO 4 , FeSO 4 , MgCl and CaCl 2 [17].…”
Section: The Martian Environmentmentioning
confidence: 99%
“…However, the stress imposed by salts different from sodium chloride is not necessarily the same. In an experimental study on epsotolerance, Crisler et al (2012) report the growth of bacterial isolates in culture media with MgSO 4 ·7H 2 O, and argue a favorable implication for Mars habitability, because sulfates are also present in this planet (Crisler et al, 2012). The adaptive strategies for tolerance at high MgSO 4 concentrations were not explored, but the authors noticed some unexplained differences in the growth rate and stationary-phase maximum densities when their isolates were exposed to different sulfate salts.…”
Section: Introductionmentioning
confidence: 99%